2013
DOI: 10.1242/dev.090043
|View full text |Cite
|
Sign up to set email alerts
|

Neuroblast pattern and identity in the Drosophila tail region and role of doublesex in the survival of sex-specific precursors

Abstract: SUMMARYThe central nervous system is composed of segmental units (neuromeres), the size and complexity of which evolved in correspondence to their functional requirements. In Drosophila, neuromeres develop from populations of neural stem cells (neuroblasts) that delaminate from the early embryonic neuroectoderm in a stereotyped spatial and temporal pattern. Pattern units closely resemble the ground state and are rather invariant in thoracic (T1-T3) and anterior abdominal (A1-A7) segments of the embryonic ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 99 publications
2
74
0
Order By: Relevance
“…Many SAbg neurons are lost in dsx-null males, and a subset is gained in dsxnull females (Billeter et al, 2006). Underlying this is the induction of female-specific programmed cell death of posterior neuroblast lineages in females by DsxF, and their survival and lineage progression in males due to DsxM (Taylor and Truman, 1992;Billeter et al, 2006;Birkholz et al, 2013). The function of fruM is thereafter limited to activating serotonin expression in the remaining neurons (Billeter et al, 2006).…”
Section: Sexual Dimorphism Of Post-embryonic Ilp7 Neuronsmentioning
confidence: 99%
“…Many SAbg neurons are lost in dsx-null males, and a subset is gained in dsxnull females (Billeter et al, 2006). Underlying this is the induction of female-specific programmed cell death of posterior neuroblast lineages in females by DsxF, and their survival and lineage progression in males due to DsxM (Taylor and Truman, 1992;Billeter et al, 2006;Birkholz et al, 2013). The function of fruM is thereafter limited to activating serotonin expression in the remaining neurons (Billeter et al, 2006).…”
Section: Sexual Dimorphism Of Post-embryonic Ilp7 Neuronsmentioning
confidence: 99%
“…S1A-C) (Birkholz et al, 2013). We excluded NB3-3, as CCAP neurons do not express eagle (eg)-Gal4>UAS-GFP and it has been shown that eg expression is maintained by the NB3-3 lineage at least until late embryogenesis ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1A) (Bossing et al, 1996;Schmidt et al, 1997Schmidt et al, , 1999Urbach et al, 2003Urbach et al, , 2016Wheeler et al, 2009;Birkholz et al, 2013). The CNS can be subdivided into the brain and the ventral nerve cord (VNC); here, we focus on the VNC.…”
Section: Introductionmentioning
confidence: 99%